Pengaruh Market Orientation, Technology Orientation, dan Entrepreneurial Orientation Terhadap Business Performance Pada Usaha Coffee Shop [The Effect of Market Orientation, Technology Orientation, and Entrepreneurial Orientation Towards Business Performance of Coffee Shop Businesses] - Thioanda, Nataya Niken; Wardhana, Ali (Universitas Pelita Harapan, 2022)
The purpose of this study is to determine the effect of market orientation, technology orientation, and entrepreneurial orientation on business performance in the business of coffee shop. This study uses a quantitative approach where 40 coffee shops were used as sample from the results of the survey conducted. The sampling method used is non probability sampling with purposive sampling technique. Data were analyzed using multiple regression analysis method. The results of hypothesis testing with t-test explain that partially market orientation and entrepreneurial orientation have a positive and significant effect on business performance. Meanwhile, technology orientation has no significant effect on business performance. In the results of the F test, it is known that there is an effect of market orientation, technology orientation, and entrepreneurial orientation simultaneously on business performance in the business of coffee shop. Suggestions that can be conveyed in this study are coffee shop needs to implement strategies, especially market orientation and entrepreneurial orientation to understand consumer insight and take advantage of these opportunities in order to improve their business performance.Bahasa Indonesia Abstract: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh orientasi pasar, orientasi teknologi, dan orientasi kewirausahaan terhadap kinerja usaha pada usaha kedai kopi. Penelitian ini menggunakan pendekatan kuantitatif yang melibatkan 40 kedai kopi yang digunakan sebagai sampel dari hasil survei yang dilakukan. Metode pengambilan sampel yang digunakan adalah non probability sampling dengan teknik purposive sampling. Analisis data menggunakan metode analisis regresi berganda. Hasil pengujian hipotesis dengan uji-t menjelaskan bahwa secara parsial orientasi pasar dan orientasi kewirausahaan berpengaruh positif dan signifikan terhadap kinerja usaha. Sedangkan orientasi teknologi tidak berpengaruh signifikan terhadap kinerja bisnis. Pada hasil uji F diketahui bahwa ada pengaruh orientasi pasar, orientasi teknologi, dan orientasi kewirausahaan secara simultan terhadap kinerja usaha pada usaha warung kopi. Saran yang dapat disampaikan dalam penelitian ini adalah coffee shop perlu menerapkan strategi khususnya orientasi pasar dan orientasi kewirausahaan untuk memahami wawasan konsumen dan memanfaatkan peluang tersebut untuk meningkatkan kinerja usahanya.